2013
DOI: 10.1007/s10522-013-9420-0
|View full text |Cite
|
Sign up to set email alerts
|

Depression-like behavior is dependent on age in male SAMP8 mice

Abstract: Abstract:Aging is associated with an increased risk of depression in humans. To elucidate the underlying mechanisms of depression and its dependence on aging, here we study signs of depression in SAMP8 mice. For this purpose, we used the forced swimming test (FST). The total floating time in the FST was greater in SAMP8 than in SAMR1 mice at 9 months of age; however, this difference was not observed in 12-month-old mice, when both strains are considered elderly. Of the two strains, only the SAMP8 animals respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
6
1
Order By: Relevance
“…Previously it has been demonstrated that serotonin receptor densities such as 5-HT 2A did not suffer changes with age in SAMR1 compared to SAMP8 mice, whereas SERT increases at 9 months of age [31]. Regarding the serotoninergic system, here, we did not observe any significant change in gene expression of serotonin receptors and SERT protein levels after MCR5 treatment.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Previously it has been demonstrated that serotonin receptor densities such as 5-HT 2A did not suffer changes with age in SAMR1 compared to SAMP8 mice, whereas SERT increases at 9 months of age [31]. Regarding the serotoninergic system, here, we did not observe any significant change in gene expression of serotonin receptors and SERT protein levels after MCR5 treatment.…”
Section: Discussioncontrasting
confidence: 54%
“…Besides the age-related cognitive decline that mainly characterizes the SAMP8 model, this strain also displays anxiety-and depressive-like behaviour in comparison to their senescence-acceleration resistant counterparts, SAMR1 mice [28]. In particular, the SAMP8 mouse presents alterations in the serotoninergic system and BDNF expression, calcium signalling pathways and increased neuroinflammation that lead to the development of BPSD and in particular depressive-like behaviour [31]. Collectively, therefore it is believed that this rodent model is appropriate for studying depressive-like behaviour in an aged population with cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 5-HT system dysfunction results in diarrhea-predominant irritable bowel syndrome (D-IBS), in which the gastrointestinal motility and viscera sensitivity are increased (Siegert and Nieber, 2010; Grenham et al, 2011). The 5-HT 1A receptor is one of the most important 5-HT receptors related to depression (Pérez-Cáceres et al, 2013), anxiety (Podona et al, 1994), and stress-induced dyspeptic ulcers and anxiety (Podona et al, 1994). Therefore, targeting at 5-HT neurotransmitter and its 5-HT 1A receptor may be a promising approach for treatment of IBS-like symptoms including psychiatric and gastrointestinal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by an early onset of age-related alterations, such as hair loss, dull hair, and short lifespan [ 21 ]. SAMP8 mice are comparable to normal SAMR1 mice before four months of age, but SAMP8 mice exhibit significant emotional and memory impairments after six months of age; thus, the onset of impairments occurs considerably earlier in SAMP8 mice than in normal SAMR1 mice [ 22 , 23 , 24 , 25 ]. Rhea and Banks (2017) confirmed the appropriateness of SAMP8 mice as an animal model for studies on age-related emotion and memory dysfunction [ 26 ].…”
Section: Introductionmentioning
confidence: 99%